Fertility control: update and trends - Rabe, Thomas; Runnebaum, Benno (Springer Berlin Heidelberg, 1999)
The name of Benno Runnebaum is closely tied to the status of gynaecological endocrinology and reproductive medicine and so it seemed appropriate to dedicate this conference book entitled "Fertility Control" to him in recognition of his achievements. His clinical and research work is reflected in more than 450 original scientific publications and many young scientists and doctors from home and abroad have received their further clinical and scientific training in his department. With this volume we would all like to thank Professor Runnebaum as a mentor and friend for his achievements in the field of gynaecological endocrinology and reproductive medicine